Portraits croisés d’une gardienne d’autel et d’un tailleur d’amulettes, artisans des cultes à la Santa Muerte au Mexique et au San la Muerte en Argentine - Maureen Burnot (Terrains/Théories)
This article compares two versions of the informal and controversial cult of the image of Death in Latin America, Santa Muerte in Mexico and San la Muerte in Argentina. From the crossed portraits of two key figures of the ritualisation and the spreading of these cults, it sheds light on the essential role that iconographic objects have, their manufacture as foundations of legitimacy of the two ritual specialists. Ethnography also reveals the improvised character of their practice and the ability of the two manufacturers to give and take care of the community of the faithful and their Saint. Their legitimacy appears socially multi-located between popular followers, from marginal backgrounds, and representatives of the media and the artistic and heritage milieu. The article analyses the influence and prestige of these « artisans » of the cult and proposes to shad light on the logic of adherence and spreading of these devotions through the biographical and sociological profile of its leading figures.